Characteristics of Terrorism - Karen Pittel; Dirk Rübbelke (ETH Zurich, CER-ETH - Center of Economic Research, 2009)
Individual terrorist are frequently behaving seemingly absurd, e.g. by carrying out suicide operations, while activities of the terrorist organisations as a whole often seem to be conducted in a very effective way. These facts caused many researchers to regard the leaders representing the organisations like rational entities, while the followers are supposed to be just obeying and, hence, to be irrational. In this paper we offer a different approach which postulates rationality of all involved agents. We demonstrate how these agents' behaviour could be modelled, while taking into account options of the terrorist leaders to influence their followers. From our model approaches to counter terrorism on both the leadership as well as the follower level can be derived.
Keywords: D74; D69; 330; cognitive dissonance; joint production; Lancastrian characteristics approach; public goods; rationality; suicide attacks; terrorism; Terrorismus; Rationalität; Arbeitsgruppe; Organisationsstruktur; Intertemporale Entscheidung; Entscheidung unter Unsicherheit; Theorie